Ductile-regime machining model for ultrasonic elliptical vibration cutting of brittle materials. (December 2018) - Huang, Weihai; Yu, Deping; Zhang, Xinquan; Zhang, Min; Chen, Dongsheng
Abstract: Ultrasonic elliptical vibration cutting (UEVC) is attracting much attention in ultra-precision machining of brittle materials as it was found be able to effectively increase the critical depth of cut ( dc ) of brittle materials. However, the mechanisms for the increased dc are still not fully understood. In this study, a ductile-regime machining model was developed for the UEVC of brittle materials to achieve maximum dc and thus the maximum machining efficiency. It shows that the reasons for the increase of dc are: (1) The actual undeformed chip thickness (UCT) is smaller than the nominal depth of cut (DOC); (2) The distance from transient surface to target surface (DTSTS) can endure the crack propagation within a certain range when UCT exceeds the critical UCT ( tc ). Based on the ductile-regime machining model, a predictive model was developed for the determination of dc in microgroove plunge-cutting with respect to several determining factors, including DTSTS, UCT, tc and length of the crack ( Cm ). A series of experiments on plunge-cutting of KDP crystal were conducted. Results showed that the predicted dc match well with the experimental ones. In addition, it was found that dc increases as the amplitude of vibration along the cutting direction increases or the cutting speed decreases, and dc increases first and then decreases as the amplitude of vibration along the thrust direction increases.